Regional Differences in the Starting Wage of Master’s vs. Bachelor’s Degree Graduates: Empirical Evidence from the Hungarian Graduate Career Tracking Survey 2012 - Kun, András István (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The study examines the wage gap between bachelor‟s and master‟s degree graduates in the Hungarian labour market by NUTS2 regions. The databases used in the study have been gained from the Hungarian Graduate Career Tracking Survey conducted in 2012 as well as from public regional data sources of the Hungarian Central Statistical Office. Relying on these databases independent t-tests, variance and regression analyses are performed to 1) identify the starting wage premium of those graduated at master‟s level compared to others owning only a bachelor‟s degree in the regions of Hungary, and to 2) define the role of regional factors (economic development, labour market indicators, demographic variables) in the wage differences. Major conclusions of the study are that 1) obtaining a master‟s degree forecasts a significantly higher starting wage in most of the observed geographical areas, but 2) the size of this positive contribution significantly differs region by region (partly depending on economic and labour market factors).